Mendelian randomization supports genetic liability to hospitalization for COVID-19 as a risk factor of pre-eclampsia - Wu, Weizhen; Zhang, Junning; Qiao, Yizhuo; Ren, Yuehan; Rao, Xuezhi; Xu, Zhijie; Liu, Baoxing (Frontiers in Cardiovascular Medicine, 2024)
Background. Pre-eclampsia and eclampsia are among the major threats to pregnant women and the fetus, and can be prevented and early screened. Existing observational research presents conflicting evidence on the causal effects of COVID-19 on pre-eclampsia risk. Through Mendelian randomization, this study aims to investigate the causal effect of three COVID-19 severity phenotypes on the risk of pre-eclampsia and eclampsia, in order to provide more rigorous evidence.Summary-level data from genome-wide association studies (GWAS) of European ancestry were acquired from the GWAS catalog and Finngen databases. Single nucleotide polymorphisms (SNPs) associated with COVID-19 traits at P<5e-08 were obtained and pruned for linkage disequilibrium to generate instrumental variables for COVID-19. Inverse variance weighted (IVW) estimates were used as the primary MR results, with weighted median and MR-Egger as auxiliary analyses. Robustness of the MR findings was also evaluated through sensitivity analyses. Bonferroni correction was utilized for primary results, with a P<0.0083 considered as significant evidence, and a P within 0.083-0.05 considered as suggestive evidence.Results. Critical ill COVID-19 (defined as hospitalized for COVID-19 with death outcome or respiratory support, OR [95%